Long-Term Efficacy and Safety of Pediatric Prolonged-Release Melatonin for Insomnia in Children with Autism Spectrum Disorder - Maras, Athanasios; Schroder, Carmen M.; Malow, Beth A.; Findling, Robert L.; Breddy, John; Nir, Tali; Shahmoon, Shiri; Zisapel, Nava; Gringras, Paul (Journal of child and adolescent psychopharmacology, 2018)
A recent double-blind randomized placebo-controlled study demonstrated 3-month efficacy and safety of a novel pediatric-appropriate prolonged-release melatonin (PedPRM) for insomnia in children and adolescents with autism spectrum disorder (ASD) and neurogenetic disorders (NGD) with/without attention-deficit/hyperactivity disorder comorbidity. Long-term efficacy and safety of PedPRM treatment was studied. A prospective, open-label efficacy and safety follow-up of nightly 2, 5, or 10 mg PedPRM in subjects who completed the 13-week double-blind trial (51 PedPRM; 44 placebo). Measures included caregiver-reported Sleep and Nap Diary, Composite Sleep Disturbance Index (CSDI), caregiver's Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale, and quality of life (WHO-5 Well-Being Index). Ninety-five subjects (74.7% males; mean [standard deviation] age, 9 [4.24]; range, 2-17.5 years) received PedPRM (2/5 mg) according to the double-blind phase dose, for 39 weeks with optional dose adjustment (2, 5, or 10 mg/day) after the first 13 weeks. After 52 weeks of continuous treatment (PedPRM-randomized group) subjects slept (mean [SE]) 62.08 (21.5) minutes longer ( = 0.007); fell asleep 48.6 (10.2) minutes faster ( < 0.001); had 89.1 (25.5) minutes longer uninterrupted sleep episodes ( = 0.001); 0.41 (0.12) less nightly awakenings (>50% decrease; = 0.001); and better sleep quality ( < 0.001) compared with baseline. The placebo-randomized group also improved with PedPRM. Altogether, by the end of 39-week follow-up, regardless of randomization assignment, 55/72 (76%) of completers achieved overall improvement of ≥1 hour in total sleep time (TST), sleep latency or both, over baseline, with no evidence of decreased efficacy. In parallel, CSDI child sleep disturbance and caregivers' satisfaction of their child's sleep patterns ( < 0.001 for both), PSQI global ( < 0.001), and WHO-5 ( = 0.001) improved in statistically significant and clinically relevant manner ( = 72) compared with baseline. PedPRM was generally safe; most frequent treatment-related adverse events were fatigue (5.3%) and mood swings (3.2% of patients). PedPRM, an easily swallowed formulation shown to be efficacious versus placebo, is an efficacious and safe option for long-term treatment (up to 52 weeks reported here) of children with ASD and NGD who suffer from insomnia and subsequently improves caregivers' quality of life.